Optimal channel multiplexing and maximal ratio combining: CINR comparison - V. P. Tuzlukov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Comparison between two common spatial combining algorithms, namely, optimal combining (OC) and maximal ratio combining (MRC) is carried out based on definition of a gain ratio. The receive carrier-to-interference plus noise ratio (CINR) is applied in Raleigh fading wireless communication systems to define the gain CINROC/CINRMRC with multiple interferences when the generalized approach to signal processing in noise is employed. The exact expression for the probability density function (pdf) and analytical solution for the average gain CINROC/CINRMRC in the case of a single interference is derived. For multiple interferences Monte-Carlo simulation to define the pdf and gain CINROC/CINRMRC is used. Additionally, an upper bound to the gain CINROC/CINRMRC to determine when the OC will exhibit significant gains over MRC is derived.